2017
DOI: 10.1093/biolre/iox138
|View full text |Cite
|
Sign up to set email alerts
|

Germline competency of human embryonic stem cells depends on eomesodermin

Abstract: In humans, germline competency and the specification of primordial germ cells (PGCs) are thought to occur in a restricted developmental window during early embryogenesis. Despite the importance of specifying the appropriate number of PGCs for human reproduction, the molecular mechanisms governing PGC formation remain largely unexplored. Here, we compared PGC-like cell (PGCLC) differentiation from 18 independently derived human embryonic stem cell (hESC) lines, and discovered that the expression of primitive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
107
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(113 citation statements)
references
References 48 publications
4
107
0
Order By: Relevance
“…Remarkably, this variation was positively correlated with the expression levels of T and EOMES , with higher expression of said factors reflected in enhanced differentiation potential of the clone (Yokobayashi et al, ). This correlation was reproduced in hESCs induced with a 4i‐primed intermediate stage, and additional differentiations with EOMES mutant cells showed drastic reduction in hPGCLC specification, hinting that early mesoderm‐associated transcription factors are necessary at least for the initial step of hPGCLC commitment (Figure ) (Chen et al, ). Exactly how the presence of factors such as T and EOMES engenders permissiveness of BMP‐responding cells remains to be clarified.…”
Section: Mechanisms In Pgc Development: the Human Perspectivementioning
confidence: 84%
See 3 more Smart Citations
“…Remarkably, this variation was positively correlated with the expression levels of T and EOMES , with higher expression of said factors reflected in enhanced differentiation potential of the clone (Yokobayashi et al, ). This correlation was reproduced in hESCs induced with a 4i‐primed intermediate stage, and additional differentiations with EOMES mutant cells showed drastic reduction in hPGCLC specification, hinting that early mesoderm‐associated transcription factors are necessary at least for the initial step of hPGCLC commitment (Figure ) (Chen et al, ). Exactly how the presence of factors such as T and EOMES engenders permissiveness of BMP‐responding cells remains to be clarified.…”
Section: Mechanisms In Pgc Development: the Human Perspectivementioning
confidence: 84%
“…These data robustly demonstrated that SOX17 is necessary and sufficient for hPGC specification, placing it at the top of a genetic hierarchy driving hPGC fate in a competent milieu. Just as importantly, most other reports of in vitro hPGCLC differentiation thus far have independently verified early SOX17 expression, which has now positioned SOX17 as a major molecular footprint of nascent hPGC identity (Chen et al, ; Kobayashi et al, ; Mitsunaga et al, ; Sasaki et al, ; von Meyenn et al, ).…”
Section: Mechanisms In Pgc Development: the Human Perspectivementioning
confidence: 92%
See 2 more Smart Citations
“…They further provided immunofluorescence staining data supporting expression of EOMES in E11-E15 cynomolgus monkey embryos at the close proximity to locations of PGC specification. Using 18 human ESC clones, a group led by Amander Clark later confirmed that germline competency of human ESCs is also dependent on expression of EOMES (23). Overall, the study of Kojima et al provided critical pieces of information to understand similarities and differences in transcriptional mechanisms involved in PGC specification.…”
mentioning
confidence: 99%